Implementasi Konseling Klasikal dengan Metode Kisah dalam Mengembangkan Kecerdasan Emosional Peserta Didik di MA - Muhammad Muzakkir Abid; Neni Noviza; Lena Marianti (Scidacplus, 2025)
Emotional intelligence is a critical factor that determines students' success in coping with academic pressure, building social relationships, and managing themselves healthily. This study aims to describe the emotional intelligence of eleventh-grade (XI B) students at MA Darun Najah Bangun Jaya, Ogan Ilir, and to analyze the implementation of classical counseling services using the storytelling method to develop students' emotional intelligence. This study employed a qualitative field research approach, with data collected through semi-structured interviews, participatory observation, and documentation studies conducted across four meetings involving 21 students selected through purposive sampling. Data were analyzed using the Miles and Huberman interactive model, comprising data reduction, data display, and conclusion drawing, while data validity was examined through source and technique triangulation. The results indicate that before the intervention, students' emotional intelligence in the aspects of self-emotion recognition, emotion management, self-motivation, empathy, and social relationship building was underdeveloped, characterized by high temperament, anxiety, and difficulty managing interpersonal conflict. The implementation of classical counseling with the storytelling method was carried out through seven stages: the initial stage, needs identification, method determination, service delivery, counseling preparation, tool/media preparation, and outcome evaluation. Following the intervention, students demonstrated improved emotional self-awareness and regulation, more stable self-motivation, and more effective social relationship skills. This study implies the importance of integrating the storytelling method, particularly Qur'anic narratives, as a contextual classical counseling strategy aligned with Islamic values in the madrasah environment.